The effect of organizational citizenship behavior (OCB) and work life balance (WLB) on turnover intention of generation Z workers in Semarang City - Auliya Putri Nur Kholifah; Suhana Suhana (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the influence of Organizational Citizenship Behavior (OCB) and Work–Life Balance (WLB) on turnover intention among Generation Z employees in Semarang. Rising turnover intention among Generation Z workers has emerged as a critical organisational challenge, particularly as this cohort demonstrates distinct workplace expectations regarding recognition, flexibility, and career fulfilment. Employing a quantitative research design, the study collected data through structured questionnaires administered to 191 Generation Z employees working across various sectors in Semarang City. The data were analysed using multiple linear regression with the assistance of IBM SPSS Statistics. The findings reveal that Organizational Citizenship Behavior exerts a positive and significant effect on turnover intention, suggesting that employees who frequently engage in extra-role behaviours may experience increased dissatisfaction or emotional strain when such contributions are not adequately recognised or rewarded by the organisation. In contrast, Work–Life Balance was found to have no significant influence on turnover intention within the study context. These findings highlight the importance of organisational appreciation, recognition systems, and equitable treatment in retaining Generation Z employees. The study provides practical implications for human resource management, particularly in designing employee retention strategies that acknowledge voluntary employee contributions and align with the evolving expectations of younger workforce generations. Furthermore, the research contributes to the growing literature on generational workforce behaviour, employee retention, and organisational management in emerging economy contexts. Keywords: Organizational Citizenship Behavior; Work Life Balance;Turnover Intention